Mapping the distribution of bioactive compounds and aroma/flavour precursors in green coffee beans with an integrated mass spectrometry-based approach - Bindi, Greta; Smith, Andrew; Crisafulli, Paola; Solano Sánchez, William; y otros más. (De Gruyter, 2024)
Coffee is one of the most enjoyed beverages worldwide and whilst a wide array of secondary metabolites has been qualitatively and quantitatively characterised within the coffee bean, little is known about their distribution in different bean tissues. In this work, complementary mass spectrometry (MS) based approaches were utilised to determine the spatial metabolomic content of coffee beans, focusing on highlighting those which presented a regiospecific distribution and distinguished the different endosperm regions and the embryo. Preliminary exploration of the spatial metabolome of Coffea arabica coffee beans highlighted tissue-specific molecular features through an unsupervised statistical analysis. Then, the complementary information derived from higher resolution MS approaches resulted in the annotation of 13 metabolites which showed a specific enrichment in at least one tissue, and most of these were noted to be bioactive compounds or aroma/flavour precursors. Knowledge of the tissue distribution of these compounds could shed light on their biological role in plant physiology and bean development, but could also have relevant implications for their positive impact on human health due to coffee consumption as well as their possible effect on aroma and flavour upon roasting of green coffee beans.